Police Barracks - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, Trinidad, 2010)
Exterior view of the Police Barracks/Police Headquarters building at the corner of St. Vincent and Sackville Streets, Port of Spain, Trinidad. There are several persons walking on the streets outside the building.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Police stations--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Fences--Trinidad and Tobago